Proposed new design scheme of LeRun Bike Centre for LeRun Industries Sdn. Bhd. at Lot 264, Jalan Ampang Off Jalan Jelatek, 50450 Kuala Lumpur / Noor Nadia Ahmad - Ahmad, Noor Nadia (Faculty of Architecture, Planning and Surveying, 2009)
The competitive environment in retail and bicycle industry is expected to get more intense. There are lot of bicycle retails have been set up in every states in Malaysia and more are still to come. To succeed in this business, retailers will have to rethink their existing work practices and business strategies to see if more efficiencies and competitive advantage can be secured by doing things differently. This proposal is to open new concept store of LeRun Bike Centre at Jalan Ampang off Jalan Jelatek, Kuala Lumpur. The main objective is to introduce a ‘Dynamic’ concept and ‘Modern’ design to follow the client corporate image and identity. This centre is different from other bicycles retail. It will be a hot spot for the bicycle fans and will act as a catalyst to prompt other retailers to convert a conventional setting to the current modern concept store. The idea to undertake this project was given due attention after taking into consideration the current and design issues, and to solve the problems encountered by the bicycle retails efficiently. Therefore, a plan was proposed to prepare new design and approach that may interest and fulfill the aspiration of the client, workers and customer. Design scheme concept should be taken into account as profoundest study. From the research and observation conducted, all data and details gathered was used as a guideline in the design process.